Copper, zinc and lead isotope signatures of sediments from a mediterranean coastal bay impacted by naval activities and urban sources. (December 2019) - Araújo, Daniel F.; Ponzevera, Emmanuel; Briant, Nicolas; Knoery, Joël; Bruzac, Sandrine; Sireau, Teddy; Brach-Papa, Christophe
Abstract: Toulon bay is severely impacted by metal contamination induced by past and recent naval activities. In this work, Cu, Zn and Pb isotope compositions and elemental concentrations of fifty-five surface sediments were determined in order to map the spatial distribution of anthropogenic and natural sources along this land-sea continuum. Two sub-systems of Toulon Bay, the Small and Large bays, showed well-marked patterns on metal contamination levels and isotope signatures for Cu and Pb. The Small bay had the highest metal concentrations, and displayed average Pb and Cu isotope compositions of 1.1664 ± 0.0043 (1s, expressed as 206 Pb/ 207 Pb ratios) and −0.17 ± 0.19‰ (1s, expressed as δ 65 CuNIST values), respectively. It contrasted with the Large bay, with moderate to pristine metal concentrations and average Pb and Cu isotope compositions of 1.1763 ± 0.0079 (1s) and +0.08 ± 0.23‰ (1s), respectively. Lead isotope systematics indicated a binary source mixing process involving industrial and natural sources, while Cu isotope systematics showed a ternary mixing process involving two distinct anthropogenic signatures, interpreted as associated to new diffuse anthropogenic sources and old warfare material. In contrast, Zn isotope compositions in the Small and Large bays were practically the same: +0.06 ± 0.05‰ and +0.06 ± 0.11‰ (1s, expressed δ 66 ZnJMC values), respectively, denoting an overlap between isotope signatures of natural and anthropogenic sources. This study presents the first detailed spatial distributions of Cu and Zn isotope compositions for an aquatic system, and demonstrates the feasibility to use Cu isotopes as tracers of anthropogenic sources in coastal environments. Highlights: Cu isotope systematic show a mixing process of natural and anthropogenic sources. Low Cu contaminated sediments display δ 65 CuNIST values ranging from 0.0 to +0.2‰. Contaminated sediments by diffuse sources tend to negative δ 65 CuNIST values. Pb isotopes reveal mixing process involving industrial and natural sources. Zn isotope system does not allow identifying mixing source processes.